2010
DOI: 10.1016/j.bbamem.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by CRAMP of the responses of murine peritoneal macrophages to extracellular ATP

Abstract: Peritoneal macrophages were isolated from wild type (WT) mice and from mice invalidated for the P2X(7) receptor (KO) which had been pretreated with thioglycolate. In cells from WT mice, 1 mM ATP increased the intracellular concentration of calcium ([Ca(2+)](i)), the uptake of ethidium bromide, the production of reactive oxygen species (ROS), the secretion of IL-1beta, the release of oleic acid and of lactate dehydrogenase; it decreased the intracellular concentration of potassium ([K(+)](i)). In KO mice, ATP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…These authors also reported that the score for LL17-37, the C-terminal fragment of LL-37, was close to 3. In line with this result, the C-terminal fragment of LL-37 formed an ␣-helix (36).…”
Section: Discussionsupporting
confidence: 70%
“…These authors also reported that the score for LL17-37, the C-terminal fragment of LL-37, was close to 3. In line with this result, the C-terminal fragment of LL-37 formed an ␣-helix (36).…”
Section: Discussionsupporting
confidence: 70%
“…Both the human LL-37 and the murine CRAMP (cathelicidin-related antimicrobial peptide, an orthologue of human LL-37) have been shown in vitro to reduce the activation of IL-1␤ by the Nlrp3 inflammasome in macrophages (Pochet et al, 2006;Seil et al, 2010;Hu et al, 2014). In all of these cases, ATP activated the inflammasome protein complex and inhibition was achieved via interaction of the cathelicidin peptide with the receptor for ATP, P2X7.…”
Section: Inhibition Of Lysosomal Dependent Nlrp3 Activationmentioning
confidence: 96%
“…The human antimicrobial peptide LL-37 can potentiate both human and mouse P2X7 activation (Elssner et al, 2004). In contrast, the murine antimicrobial peptide CRAMP can enhance human but impair murine P2X7 activation (Seil et al, 2010). The antibiotic polymyxin B can potentiate human P2X7 activation (Ferrari et al, 2004), whereas the antiparasitic ivermectin can potentiate human but not murine P2X7 (Norenberg et al, 2012).…”
Section: Modulators Of P2x7 Receptor Activationmentioning
confidence: 99%